To determine which of the given points lies on the graph described by the function \( y = (2x + 1)^2 - 4 \), we need to substitute the x-coordinates of each point into the function and see if the resulting y-value matches the y-coordinate of the point.
Let's evaluate the function for each x-coordinate from the choices provided:
-
For the point \((-1, -5)\): \[ y = (2(-1) + 1)^2 - 4 = (-2 + 1)^2 - 4 = (-1)^2 - 4 = 1 - 4 = -3 \] The point \((-1, -5)\) does not lie on the graph.
-
For the point \((0, -2)\): \[ y = (2(0) + 1)^2 - 4 = (0 + 1)^2 - 4 = 1^2 - 4 = 1 - 4 = -3 \] The point \((0, -2)\) does not lie on the graph.
-
For the point \((1, 2)\): \[ y = (2(1) + 1)^2 - 4 = (2 + 1)^2 - 4 = 3^2 - 4 = 9 - 4 = 5 \] The point \((1, 2)\) does not lie on the graph.
-
For the point \((-1, -3)\): \[ y = (2(-1) + 1)^2 - 4 = (-2 + 1)^2 - 4 = (-1)^2 - 4 = 1 - 4 = -3 \] The point \((-1, -3)\) does lie on the graph.
Thus, the correct point on the graph is \((-1, -3)\).